Agricultural waste byproduct utilization: date pit powder 1H NMR metabolite identification for goat (Capra hircus) milk pathway analysis - Rahman, M.R.Abd; Aween, M.M.; Hassan, Z.; Hassan, M.S.; Hashim, R.; Ismail, I.S.; Misenan, M.S.M.; Ranjithkumar, R.; Li, K.F.; Wong, L.S. (Elsevier, 2025)
Agricultural waste byproducts (Date pits), are discarded in tons yearly and possess several nutritional advantages. Researches indicated that goat milk holds equivalent or superior potential than cow milk. Pathway analyses aid in uncovering biological mechanisms embedded within the dataset. This study concentrated on date pit powder (DPP) as a potential supplement for dairy goats to enhance milk quality, emphasizing on the route analyses. 1H NMR analyses on DPP extracts was executed followed by chemometrics. Dairy goats were categorized into six groups (n = 4 / group): control, 10 g and 20 g for both Ajwa DPP (high quality) and Mariami DPP, and an additional 30 g for Mariami DPP exclusively. DPP supplementation was administered daily throughout a three-month duration. The goat milk was subsequently subjected to 1H NMR studies, followed by chemometrics (PCA and PLS). Milk metabolites were subsequently analyzed using MetaboAnalyst software, with visualizations shown as heatmaps and pathway analyses. The 1H NMR data of DPP samples from TCA and PB extracts (non-polar) successfully eliminated most metabolites in comparison to the aqueous ACN and MeOH extracts (polar). Following which, Ajwa and Mariami DPP exhibited nearly identical concentrations of the chemicals α-Glucose and flavanone, resulting in PCA clustering. The heatmap revealed varying milk metabolite concentrations, reflecting the animals' condition at months 1 and 3 due to DPP treatment. Six significant metabolic pathways (p < 0.05), with alanine, aspartate, and glutamate metabolism exhibiting the lowest p-value. DPP, an agricultural waste byproduct, is a viable alternative nutritional supplement at enhancing milk quality, as evaluated by metabolic pathways, in addition to reports of increased milk yield in other studies. This indirectly is in line with the sustainable development goals (SDG) in particular targeting on zero hunger; and good health and well-being.